Human placental growth hormone is increased in maternal serum at 20 weeks of gestation in pregnancies with large-for-gestational-age babies. (1st November 2016) - Liao, Shutan; Vickers, Mark H.; Taylor, Rennae S.; Jones, Beatrix; Fraser, Mhoyra; McCowan, Lesley M. E.; Baker, Philip N.; Perry, Jo K.
Abstract: To investigate the relationship between maternal serum concentrations of placental growth hormone (GH-V), insulin-like growth factor (IGF)-1 and 2, IGF binding proteins (IGFBP)-1 and 3 and birth weight in appropriate-for-gestational-age (AGA), large-for-gestational-age (LGA) and small-for-gestational-age (SGA) cases in a nested case-control study. Maternal serum samples were selected from the Screening for Pregnancy Endpoints (SCOPE) biobank in Auckland, New Zealand. Serum hormone concentrations were determined by ELISA. We found that maternal serum GH-V concentrations at 20 weeks of gestation in LGA pregnancies were significantly higher than in AGA and SGA pregnancies. Maternal GH-V concentrations were positively correlated to birth weights and customized birth weight centiles, while IGFBP-1 concentrations were inversely related to birth weights and customized birth weight centiles. Our findings suggest that maternal serum GH-V and IGFBP-1 concentrations at 20 weeks' gestation are associated with fetal growth.